Body Surface Laplacian Mapping of Bioelectrical Activity - He, B.; Yu, X.; Wu, D.; Mehdi, N. (Methods of Information in Medicine, 1997)
A method is described to process and interpret multi-channel bioelectrical signals. The bioelectrical signals were recorded noninvasively over the body surface of human subjects at 120 sites. The body surface Laplacian maps were then constructed from the multi-channel bioelectrical potential measurement. The method was evaluated by means of computer simulations, and applied to imaging cardiac electrical activity. The present investigation suggests body surface Laplacian mapping provides an important means in interpreting bioelectrical signals.
Keywords: Body Surface Laplacian Mapping; BSLM; BSPM; Electrocardiography